2017
DOI: 10.1149/2.1321702jes
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Successive Ionic Layer Adsorption and Reaction (s-SILAR) Method for Growth of Porous BiVO4Thin Films for Photoelectrochemical Water Oxidation

Abstract: Since monoclinic bismuth vanadate (BiVO4) has been considered to be a promising anode material for photoelectrochemical (PEC) water splitting, the synthesis of high-quality BiVO4 photoanodes for use in PEC cells is beneficial. Here, we report a facile simplified successive ionic layer adsorption and reaction (s-SILAR) method to synthesize porous BiVO4 films. Evaluation of the porous BiVO4 film as a photoanode yielded photocurrents of ∼0.70 and ∼1.20 mA cm−2 at 1.23 V vs RHE under AM1.5G irradiation for water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…■ DEVELOPMENT OF BIVO 4 ON PEM−PEC SUITABLE SUBSTRATES BY S-SILAR In the literature, BiVO 4 thin films have been deposited by various methods including electrochemical deposition, 20,34 spin-coating, 35 reactive sputtering, 36 dip-coating, 37,38 and hydrothermal methods. 39 Out of these, electrochemical deposition of BiVO 4 on FTO-coated glass substrate has been the most successful with the highest current density and stability reported so far.…”
Section: ■ Rational Designing Of the Photoelectrodes For Membrane Ele...mentioning
confidence: 99%
See 2 more Smart Citations
“…■ DEVELOPMENT OF BIVO 4 ON PEM−PEC SUITABLE SUBSTRATES BY S-SILAR In the literature, BiVO 4 thin films have been deposited by various methods including electrochemical deposition, 20,34 spin-coating, 35 reactive sputtering, 36 dip-coating, 37,38 and hydrothermal methods. 39 Out of these, electrochemical deposition of BiVO 4 on FTO-coated glass substrate has been the most successful with the highest current density and stability reported so far.…”
Section: ■ Rational Designing Of the Photoelectrodes For Membrane Ele...mentioning
confidence: 99%
“…In the literature, BiVO 4 thin films have been deposited by various methods including electrochemical deposition, , spin-coating, reactive sputtering, dip-coating, , and hydrothermal methods . Out of these, electrochemical deposition of BiVO 4 on FTO-coated glass substrate has been the most successful with the highest current density and stability reported so far. , However, the electrochemical deposition method is sensitive to the electrolyte purity, environment, and applied bias.…”
Section: Development Of Bivo4 On Pem–pec Suitable Substrates By S-silarmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of metal vanadates is a perfect example to elucidate this aspect. SILAR-based metal vanadates recently highlighted include Cu 2 V 2 O 7 , [168] Ag 3 VO 4 , [169] BiVO 4 , [170,171] and Fe 2 V 4 O 13 , [172] which have all been mostly employed as the light active materials for photoelectrochemical water splitting. Commonly in all of these, a soluble salt of the desired metal constitutes the cationic precursor while in most cases, ammonium or sodium vanadates were utilized as the vanadium precursor in the deposition process.…”
Section: Ternary Oxidesmentioning
confidence: 99%
“…Due to the insolubility of Bi(NO 3 ) 3 in water, acid was added to the bismuth precursor to assist the dissolution. Guo et al [170] used acetic acid or acetic acid/water mixture as the solvent to prepare the Bi bath and SEM images revealed that the BiVO 4 film prepared via acetic acid was dense while it was much more porous if using mixture of water and acetic acid as the solvent for Bi(NO 3 ) 3 . BiVO 4 films prepared from different cycles were investigated in PEC performances and the optimized cycle was 20 and the best annealing temperature was 450 °C.…”
Section: H O 4h 4e Omentioning
confidence: 99%